Sister Wendy's story of painting modernism ([London] BBC Video, 1996)
Sister Wendy Beckett traces the development of 20th century art and its legacy to the future.
VHS format.
Keywords: Painting, European; Painting, American; Painting, Modern -- 19th century; Painting, Modern -- 20th century